Reducing dependency and promoting community participation in development?: Four case studies of participatory rural appraisal and community action plans in Botswana - Dipholo, Kenneth (My University, 2008)
ABSTRACT Since independence in 1966, centralized development planning has ensured the availability of basic facilities and services in rural areas of Botswana but has also contributed to over-reliance on the government for the majority of rural people. The consequence of this centralized and accelerated approach to rural development has been the exclusion of rural communities from planning and implementation of facilities meant to benefit them. The international debate on sustainable rural development led the Botswana government to re-think its rural development policy with a view to establishing more effective strategies for rural development. The Community Based Strategy for Rural Development, introduced in 1997 emphasizes the important role of communities in their own development, by promoting Participatory Rural Appraisal (PRA). This study sought to discover insights into the implementation of PRA in Botswana by questioning extension workers and community members in four villages about the application and impact of PRA on their communities. The research uses the frameworks of qualitative research and critical adult education theory to enquire into the basis for participatory rural development in Botswana and the implementation of Community Action Plans (CAPs). Case studies of the four villages were conducted to illuminate problematic areas of programme design and implementation. Interviews with thirty-two people and observations were the main methods of collecting data. Documents, reports and records on PRA training and application in the four villages and from outside were consulted. The research results show that the application of PRA in the participating villages has had negligible impact in reversing the state-dominated approach to development. PRA facilitators seem disinterested in its application and sustenance. However, the findings also suggest that PRA application in Botswana is not hopeless, but needs a different kind of investment, for example, introducing measures of accountability, addressing paternalistic attitudes among development workers, and exploiting key principles of adult education.
Keywords: participation; rural development; adult education; extension work; Botswana